A bill to facilitate the recovery of debts due from non-resident debtors (House doc. (North Carolina. General Assembly. House of Commons) ;, 1852)
1852 North Carolina House bill to facilitate the recovery of debts from non-resident debtors who have some personal estate or effects in the hand of any executor, administrator or trustee in North Carolina. The bill established the procedure and limitations for the creditors' recovery of the debts from these executors, administrators and trustees, as well as indemnifying them against any action by the debtor.